Punkty katechetyczne w diecezji łomżyńskiej po 1945 r. - Jemielity, Witold (Prawo Kanoniczne, 2004)
Before the war religion was an obligatory subject in primary and secondary schools. Just after the year 1945 it was the same, however, soon the State authorities started to open sucular schools. In the year 1951 lessons of religion were withdrawn nearly from all schools. At that time, priests started to teach children and young people in churches, chapels and in private houses. In the year 1956 lessons of religion came back to schools, however not for a long time. And again quick withdraw al of this subject was by making parents write declarations striking their children off the list of willing to learn religion and by depriving clergymen of qualifications to teach. Till the year 1961 lessons of religion were withdrawn from schools on motion of educational authorities measures and such situation was for the next thirty years. In that time, again, private lessons of religion were organized in churches, chapels and in private houses in villages. Educational authorities demanded submitting reports from so called catechetic points from Parish-Priests, however the Bishops definitely forbade them to do it. In the 70’s the State authorities abandoned the application of strict regulations in that case. Catechetic points survived till the year 1990.